What's the catch? Fiscal Policies for Fisheries in five African Countries - Giovanni Occhiali (Fondation pour les études et recherches sur le développement international (FERDI), 2022)
The taxation of fisheries: rationale and overarching debates Many low-income countries (LICs) have long struggled to increase their domestic revenue mobilisation, which is often seen as a necessary step to achieve a more sustained economic development. A wider fiscal space can lead to more funds being available for social spending and infrastructure investment, both of which are required to improve livelihood opportunities for their citizens. A decreased dependence on external aid to finance domestic policies, coupled with more frequent bargaining about revenue extraction between the government and the population, could also lead to better governance outcome.
Keywords: 330